EVOLUTION OF RISK FACTORS FOR CHRONIC NON-COMMUNICABLE DISEASES BETWEEN 2019 AND 2023 IN THE POPULATION OF THE CAPITAL OF GOIÁS (CIPEEX, 2025)
Brazil is currently undergoing an epidemiological transition, with an increase in chronic noncommunicable diseases (CNCDs or NCDs) to the detriment of infectious diseases. Given this, it is important to monitor risk factors for NCDs in places such as Goiânia. The objective of this study is to analyze the evolution of risk factors for chronic noncommunicable diseases in the capital of Goiás, from 2019 to 2023. This descriptive cross-sectional study used data from the VIGITEL system for the years 2019 and 2023, collected through telephone interviews with adults in Goiânia. Between 2019 and 2023, there was a 2.4% increase in the total number of smokers, especially among women (2.8%), although the prevalence remained higher among men. There was a 0.9% reduction in passive smokers in the home, but exposure to secondhand smoke at work remained a concern. Also, overweight increased by 2.3%, although obesity decreased by 1.8%. There was a decrease in the intake of healthy foods and ultra-processed foods, with a 6.4% drop in daily consumption of fruits and vegetables. In addition, insufficient physical activity decreased by 6.7%. Excessive alcohol consumption increased among men and decreased among women. The prevalence of diabetes increased by 2.2%, especially among women, while hypertension did not show significant changes. Statistical calculations indicate that the variables analyzed in general did not change significantly. Therefore, risk factors for NCDs represent a significant challenge in Goiânia. Consequently, effective public policies are essential to mitigate the impact of these diseases on its population.
Keywords: Chronic noncommunicable diseases; Risk factors; Public health